Quantitative Research Methods for Linguists: A questions and answers approach for students, 1st edition - Tim, Grant (Routledge, 2020)
Quantitative Research Methods for Linguistics provides an accessible introduction to research methods for undergraduates undertaking research for the first time. Employing a task-based approach, the authors demonstrate key methods through a series of worked examples, allowing students to take a learn-by-doing approach and making quantitative methods less daunting for the novice researcher.